Updating beliefs based on observed performance: evidence from NFL head coaches - Roach, M. A.; Owens, M. F. (Journal of Sports Economics, 2024)
We utilize play-by-play data from the National Football League to examine coaching decisions on fourth down and how sensitive they are to information on situational success and their competitive environment. Prior fourth down successes and failures within a game influence coaches in a way consistent with the notion that recent information is more salient to these coaches when making decisions and a belief in in-game momentum. Coaches are more sensitive to fourth down failures than successes, and our findings suggest this sensitivity to prior failures leads to suboptimal fourth down decisions later in the game. This finding is generally driven by the behavior of coaches with a background in coaching offense, suggesting the availability heuristic is particularly potent for managers who are more involved and, perhaps, more accountable for the details of fourth down plays. We suspect these patterns are prevalent in a wide range of managerial contexts.